Pengambilan Keputusan Instruksional Guru Matematika Dalam Merancang Pembelajaran Daring Materi Himpunan - Ainnur Rohmania; Lukman Jakfar Shodiq; Mohammad Ridho’i (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2026)
This study aims to analyze the instructional decision-making of two mathematics teachers (one male and one female) in designing online lessons on sets. This qualitative comparative case study was conducted at SMPN 1 Pasirian. Subjects were selected using purposive sampling based on their experience with online teaching, educational background, digital competence, and willingness to participate. Data were collected through semi-structured interviews, virtual classroom observations, and a review of teaching modules, validated through triangulation over a two- week period. Data analysis integrated Braun & Clarke’s Thematic Analysis and Schoenfeld’s Framework through five stages: transcription, coding, theme formation, framework mapping, and verification. The research results revealed differences in instructional decision-making strategies during the stages of generating ideas, clarifying ideas, and assessing the feasibility of ideas. These differences were influenced by variations in participants’ profiles such as teaching experience, age, digital competence, and class characteristics rather than gender alone. Gender was treated as an individual case characteristic, not a primary explanatory variable or basis for generalization. Keywords: Instructional Decision-Making, Online Learning, Set Theory